ANALISIS DAMPAK KURIKULUM MERDEKA TERHADAP DISIPLIN BELAJAR ‎SISWA KELAS III MIS AL-FALAH TERATAK - Futri Zahra; Deprizon; Radhiyatul Fithri; Sakban; Salman; Cici Saputri (Jurnal Payung Sekaki : Kajian Keislaman, 2025)
his study was conducted with the aim of analyzing the effects of the implementation of the Merdeka Curriculum on the level of student discipline in the third grade at Al-Falah Teratak Islamic School. The discipline in learning is a crucial aspect that plays a role in the success of the learning process, thus it is necessary to analyze the impact of the implementation of the Merdeka Curriculum on the attitudes and behaviors of students' discipline. This research employs a quantitative method with survey as the research design. Data was collected through distributing questionnaires to 33 third-grade students who were divided into two classroom groups, namely 3A with a total of 17 students and 3B with a total of 16 students. The data analysis was conducted using descriptive statistical methods and correlation tests to evaluate the relationship between the Merdeka Curriculum and the level of learning discipline. The research findings have demonstrated that the Independent Curriculum has a significant and “positive” impact on study discipline, with a percentage of 49%. This is observed through the high level of student awareness in adhering to rules and consistency in learning. The Merdeka Curriculum contributes 25% to the learning discipline (R Square = 0.250), placing it in the "moderate" category. This discovery indicates that the Independent Curriculum has the ability to encourage students to be more responsible and disciplined in the learning process. This study recommends that schools continue to maximize the implementation of the Merdeka Curriculum to sustainably enhance the quality of students' learning discipline.